2002
DOI: 10.1051/ocl.2002.0474
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic responses and diallel analysis for an early resistance test to Sclerotinia sclerotiorum in sunflower

Abstract: Résumé : L'évaluation de la performance des génotypes du tournesol aux infections de Sclerotinia sclerotiorum permet d'identifier des nouvelles sources de résistance aux différents types d'attaque produits par ce pathogène. Les tests de résistance, menés la plupart du temps au champ, peuvent fournir des renseignements pertinents sur le niveau de résistance du matériel testé. Ce dernier pouvant ensuite permettre l'obtention de variétés hybrides. Malheureusement les protocoles d'évaluation de résistance actuelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Both additive and non-additive genetic effects influenced Sclerotinia stem rot resistance, as evidenced by significant mean squares of lines, testers, and line × tester interactions for both resistance evaluation criteria, namely, MLL and DSI. These findings are consistent with those of Khan et al [ 32 ], Disi et al [ 30 ], Godoy et al [ 59 ], Castano et al [ 60 ], and Achbani et al [ 61 ], who found that both additive and non-additive genetic action influenced Sclerotinia rot resistance inheritance and could be improved using the recurrent selection procedure. The significant effect of GCA on the sum of squares of SCA suggested that early generation selection of resistant progenies could be successful.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both additive and non-additive genetic effects influenced Sclerotinia stem rot resistance, as evidenced by significant mean squares of lines, testers, and line × tester interactions for both resistance evaluation criteria, namely, MLL and DSI. These findings are consistent with those of Khan et al [ 32 ], Disi et al [ 30 ], Godoy et al [ 59 ], Castano et al [ 60 ], and Achbani et al [ 61 ], who found that both additive and non-additive genetic action influenced Sclerotinia rot resistance inheritance and could be improved using the recurrent selection procedure. The significant effect of GCA on the sum of squares of SCA suggested that early generation selection of resistant progenies could be successful.…”
Section: Discussionsupporting
confidence: 92%
“…Kaur et al [ 53 ], Meena et al [ 54 , 55 , 56 ], Vaghela et al [ 57 ], Chaudhary et al [ 58 ], and Gupta et al [ 9 ] observed high genetic variability for yield and its component traits in Indian mustard. Godoy et al [ 59 ], Castano et al [ 60 ], Achbani et al [ 61 ], and Grecizes-Besset et al [ 62 ] in sunflower and Ferreira et al [ 63 ] in common bean revealed high genetic variability for resistance/susceptibility to S. sclerotiorum .…”
Section: Discussionmentioning
confidence: 99%
“…Sclerotinia sclerotiorum is one of the most devastating and universal plant pathogen ( 3 ). S. sclerotiorum attacks over 400 plant species worldwide including soybean ( Glycine max ), sunflower ( Helianthus annuus ) and canola ( Brassica napus ), peanut ( Arachis hypogaea ), tobacco ( Nicotiana Tabacum ), beans ( Phaseolus vulgaris ), watermelon ( Citrullus lanatus ) and alfalfa ( Medicago sativa ) ( 4 , 5 ). In Iran, this necrotrophic pathogen has been reported in commercial crops canola, strawberry ( Fragaria × ananassa ), chickpea ( Cicer arietinum ) in Dezfol, sunflower in Mazandaran, Kordestan and Azerbaijan, lettuce ( Lactuca sativa ) in Ahwaz and Andimeshk, tomato ( Solanum lycopersicum ) and eggplant ( Solanum melongena ) in Zanjan and mulberry ( Morus alba ) in Gilan province ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a great effort in searching for tolerance to midstalk rot both in cultivated sunfl ower and wild sunfl ower species. Hence, several methods of artifi cial inoculation have been developed (Degener et al 1998, Castano et al 1992b, Maširević & Gulya 1992, Grauert et al 1980, Castano et al 2002, Vasić et al 2004. To this date, a number of sunfl ower lines and hybrids with various levels of tolerance have been reported (Reimonte & Castano 2008, Rönicke et al 2004, Vear 2004), but level of tolerance is not yet considered adequate for control of the disease (Fick & Miller 1997).…”
Section: Introductionmentioning
confidence: 99%